Clinical profiles of 12 Chinese patients with diffuse panbronchiolitis - Chen, Wei; Shao, Changzhou; Song, Yuanlin; Ye, Ling; Bai, Chunxue; He, Lixian (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Diffuse panbronchiolitis (DPB) is an uncommon idiopathic inflammatory disease, characterized by chronic sinusitis, respiratory bronchiolitis and progressive airway obstruction. Without correct diagnosis and treatment, DPB may progress to bronchiectasis, respiratory failure and even death. Objective: To help other clinicians deal with DPB.Methods:Twelve Chinese patients (six women;mean (SD) age 50(14.7) years) who were diagnosed as DPB were assessed retrospectively for clinical, radiological, lung function, microbiological, and other "characteristic" laboratory parameters. Results: Most patients presented with chronic cough, copious purulent sputum production, and exertional dyspnoea, end-inspiratory crackles, and a history of sinusitis. Unlike DPB cases from Japan, cold agglutination test in 11 out of 12 patients were negative, and the CD4/CD8 lymphocyte ratio in all patients were normal or low. All patients had moderate to severe small airway disfunction and hypoxemia. The mean values of FEV1/FVC, and RV/TLC were 58.9%, and 41.5%, respectively. The most common HRCT findings from this cohort of patients were bronchiectasis and bronchiolitis, with nodular shadows distributed in a centrilobular pattern. Morphological examination revealed peribronchiolar and bronchiolar wall inflammation composed of lymphocytes, plasma cells, and histocytes. Few cases were not confirmed by diagnostic criteria from Japan but clinically diagnosed as DPB due to satisfied treatment response and typical clinical features. Conclusions:More DPB cases need to be analyzed from Chinese population due to different presentations compared to Japanese population. This experience should help other clinicians in the investigation and management of DPB in non-Japanese patients.